The long 7th century BCE at Tel Shiqmona (Israel): a high resolution chronological tool for the Levant and the Mediterranean. (4th May 2022) - Shalvi, Golan; Gilboa, Ayelet
Abstract : The 7th century in the southern Levant is characterized by Assyrian rule and subsequent Egyptian domination. Despite the relatively violent nature of this century, and abundant historical documentation, occupations both in the southern Levant and Lebanon are dated with low resolution. This deficiency was mainly created by a lack of destruction layers within this century, resulting in a dearth of chronological anchors for ceramic developments. At Tel Shiqmona, a unique purple-production centre that had been frequently destroyed, an unparalleled sequence of five layers of late Iron Age destructions/abandonments has been preserved, spanning a little over 100 years. These enable the definition of detailed typological developments of Phoenician transport jars. Being a widely distributed commercial vessel, exhibiting frequent typological changes and originating from a limited number of workshops, these jars constitute the best chronological index yet for the late Iron Age Levant. This paper presents the Tel Shiqmona sequence, outlines the typological development of the jars and explains their chronological designations. The benefits of defining archaeological sub-divisions within the 7th century BCE are highlighted by two examples: the chronology of Tyre; and settlement/geopolitical dynamics in the Assyrian province of Megiddo. It is argued that this chronological tool can be applied broadly around the Mediterranean.